Cysteine Prevents the Reduction in Keratin Synthesis Induced by Iron Deficiency in Human Keratinocytes. Issue 2 (February 2016) - Miniaci, Maria Concetta; Irace, Carlo; Capuozzo, Antonella; Piccolo, Marialuisa; Di Pascale, Antonio; Russo, Annapina; Lippiello, Pellegrino; Lepre, Fabio; Russo, Giulia; Santamaria, Rita
ABSTRACT: l ‐cysteine is currently recognized as a conditionally essential sulphur amino acid. Besides contributing to many biological pathways, cysteine is a key component of the keratin protein by its ability to form disulfide bridges that confer strength and rigidity to the protein. In addition to cysteine, iron represents another critical factor in regulating keratins expression in epidermal tissues, as well as in hair follicle growth and maturation. By focusing on human keratinocytes, the aim of this study was to evaluate the effect of cysteine supplementation as nutraceutical on keratin biosynthesis, as well as to get an insight on the interplay of cysteine availability and cellular iron status in regulating keratins expression in vitro . Herein we demonstrate that cysteine promotes a significant up‐regulation of keratins expression as a result of de novo protein synthesis, while the lack of iron impairs keratin expression. Interestingly, cysteine supplementation counteracts the adverse effect of iron deficiency on cellular keratin expression. This effect was likely mediated by the up‐regulation of transferrin receptor and ferritin, the main cellular proteins involved in iron homeostasis, at last affecting the labile iron pool. In this manner, cysteine may also enhance the metabolic iron availability for DNA synthesis without creating a detrimental condition of iron overload. To the best of our knowledge, this is one of the first study in an in vitro keratinocyte model providing evidence that cysteine and iron cooperate for keratins expression, indicative of their central role in maintaining healthy epithelia. J. Cell. Biochem. 117: 402–412, 2016. © 2015 Wiley Periodicals, Inc.